Política Pública de Comunicação e Divulgação Científica: avaliação do emprego do portal de periódicos da CAPES pelos docentes da Universidade Federal do Ceará. - Simões, Vanessa Pimenta Rodrigues (2017)
This paper deals with the evaluation of public policies in the communication and scientific dissemination areas. Its goal is to examine the use and scope of the Periodical Portal available through CAPES-MEC within the scope of the Federal University of Ceará (UFC), in an investigation that focuses specifically on the postgraduate professor. In Brazil, the access to and dissemination of scientific production has become an important public policy instrument of the Federal Government and within this line of action, the CAPES Periodicals Portal gains strong prominence. Created at the end of the year 2000, the Periodicals Portal came to serve institutions throughout the whole country. It did not have access to national and foreign scientific production, by means of a database and reference documents in all areas of knowledge. In the context of the research, of a descriptive and quali-quantitative approach, the CAPES Periodicals Portal was evaluated according to the methodology of analysis developed by the Information Literacy Competency Standards for Higher Education of the Association of College and Research Libraries (ACRL), attempting to stablish a relation from proposal goals and the effective use of this tool. The research universe, with the use of online questionaries and semistructured interviews, has covered 1310 teachers from UFC pos-graduate courses, approaching all academic fields in three campi located on Fortaleza city. The results exposed in both data collecting tools (through 117 answers from questionaries and 10 interview answers) presented consensus regarding the access and use of the tool. Nevertheless, the conclusion indicates the need for corrections regarding the simplification of the Portal interface for a better interactivity and attractiveness in the exploitation by beneficiaries, as well as actions such as continuing